PERAN MANAJEMEN PEMBIAYAAN DALAM KEBERLANGSUNGAN LEMBAGA PENDIDIKAN ISLAM DI ERA DIGITAL - Tri Yuli Lestari; Vera Astuti; Subandi; Amiruddin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Financing management is one of the crucial aspects in ensuring the sustainability of Islamic educational institutions, especially in the digital era characterized by technological disruption and changes in financial management models. This study aims to examine the strategic role of financing management in maintaining the existence and sustainability of Islamic educational institutions through the integration of digital innovation and Islamic financial principles. Using a qualitative approach with a literature study method, data were collected from various relevant scientific literature. The results of the study show that careful financial planning, diversification of financing sources, and utilization of digital technology in the fundraising and reporting system can increase the effectiveness of the institution's financial management. In addition, the application of the principles of transparency, accountability, and Islamic ethics in every financial process can build public trust and strengthen the resilience of the institution in facing various challenges. Thus, modern, adaptive, and Islamic values-based financing management is an important foundation for the sustainability of Islamic education institutions amid the dynamics of the digital era.